Growth inhibitory effects of Clary Sage(Salvia sclarea L.) on some seed germination characteristics of Red Brome (Bromus tomentellusBoiss) - ساره قمی; علی طویلی (علوم و فناوری بذر ایران, 2012)
Allelopatic interactions between plants can affect different stages of their lives. In this study, allelopathic effects of Salvia sclarea uppers, underground parts and flower extracts, in a compeletly randomized design (CRD) with 4 replications was tested on seed germination speed and percent root and shoot length, wet and dry weight of Bromus tomentellus.Five leveles of extracts including 0, 5, 25, 50 and 100% were used. Results showed the effect of upper extract was significant in germination percentage and speed, root and shoot length, dry weight of Salvia sclarea, butunderground extract was effective on all growth characteristics (Pandlt;0/01). In addition, the increasing density of extract, its inhabitation effects enhanced and subsequently decreased mean of seedling factors. Besides underground inhabitation effects of Salvia sclarea on seed germination and seedling characteristics of Bromus tomentellus were more than the above part extracts effects.